Kopf und Herz vereint zusammen Grundlinien pietistischer Hochschulbildung - Lüdke, Frank; Schmidt, Norbert (Pietas et Scientia, 2022)
How do science and faith fit together? From the very beginning, the Evangelical Church placed great value on scientific education, so that the oldest existing evangelical university was founded in Marburg as early as 1527. But what is the relationship between the Christian faith and scientific knowledge at a university that consciously wants to be evangelical? This question has been raised throughout history particularly where the spiritual renewal movement of Pietism has had an impact on higher education. To what extent can, may and should the Christian faith shape academic activities at a pietistic university? And in what way does a scientific context influence the lived faith in a Christian-oriented educational institution? The Evangelische Hochschule TABOR in Marburg organized a research conference in 2021, the results of which are presented here.